2021
DOI: 10.3389/fpubh.2021.771638
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Measures During the COVID-19 Pandemic Reduce the Spread of Other Respiratory Infectious Diseases

Abstract: Background: Public health measures (such as wearing masks, physical distancing, and isolation) have significantly reduced the spread of the coronavirus disease-2019 (COVID-19), but the impact of public health measures on other respiratory infectious diseases is unclear.Objective: To assess the correlation between public health measures and the incidence of respiratory infectious diseases in China during the COVID-19 pandemic.Methods: We collected the data from the National Health and Construction Commission in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…COVID-19, a novel coronavirus disease, has caused numerous infections worldwide. To break the transmission link of the virus and curb the outbreak of the COVID-19 pandemic, the Chinese government has taken aggressive public health monitoring and interventions, such as mass nucleic acid testing, contact tracing, travel restrictions, and avoiding crowd gathering (Cheng et al, 2021;Hu et al, 2021;Wan et al, 2022). As the Omicron variant has caused COVID-19 resurgences in many places, in cities with severe epidemics, primary and middle schools have to be closed and converted to online teaching, and colleges have implemented relatively closed-off management.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19, a novel coronavirus disease, has caused numerous infections worldwide. To break the transmission link of the virus and curb the outbreak of the COVID-19 pandemic, the Chinese government has taken aggressive public health monitoring and interventions, such as mass nucleic acid testing, contact tracing, travel restrictions, and avoiding crowd gathering (Cheng et al, 2021;Hu et al, 2021;Wan et al, 2022). As the Omicron variant has caused COVID-19 resurgences in many places, in cities with severe epidemics, primary and middle schools have to be closed and converted to online teaching, and colleges have implemented relatively closed-off management.…”
Section: Introductionmentioning
confidence: 99%
“…For example, this preventative measure, along with other mitigation strategies (physical distancing and hand hygiene) employed to reduce COVID-19, concomitantly led to a decline in influenza, enterovirus, and all-cause pneumonia cases in Taiwan ( Chiu et al, 2020 ). Similarly, another retrospective study in China and Thailand also observed a decrease in the incidence of respiratory infectious diseases, both for viral and bacterial infections, during the pandemic ( Hu et al, 2021 ; Ndeh et al, 2022 ). Granted, it is difficult to establish the independent and collective effects of the measures deployed that yielded this positive spill over.…”
Section: Benefits and Risks Associated With Wearing Face Maskmentioning
confidence: 73%
“…Some research have reported the epidemiological features of other notifiable diseases in China, such as sexually transmitted diseases and other respiratory infectious diseases, that the factors included spatial and temporal characteristics and age group distribution changed. [ 7 , 8 ] Sync with this, diarrheal cases have been found significantly reduced in England since COVID-19 control measures. [ 9 ] However, the impact of China’s measures against COVID-19 on the transmission of OID was not mentioned.…”
Section: Introductionmentioning
confidence: 86%